PER3 suppresses tumor metastasis of oral squamous cell carcinoma by promoting HIF-1α degradation - Yaoxu Li; Bing Li; Kai Yang; Lihua Zhu; Hong Tang; Yinpei Huang; Jinhai Deng; Jun Duan (Translational Oncology)
The low expression of period circadian regulator 3 (PER3) in head and neck squamous cell carcinoma is closely correlated with tumor size and invasion depth. Hypoxia-inducible factor 1 subunit alpha (HIF-1α) regulates epithelial-mesenchymal transition (EMT) transcription factors, activates EMT, and promotes tumor metastasis. Here, we investigated the role and molecular mechanism of PER3 in regulating HIF-1α and metastasis in oral squamous cell carcinoma (OSCC) by using bioinformatics analyses and in vitro and in vivo experiments. PER3 expression was decreased in OSCC, and PER3 expression was significantly negatively correlated with T stage, N stage, clinical classification, and survival time. PER3 overexpression inhibited, while PER3 knockdown prompted EMT and metastasis of OSCC cells. HIF-1α reversed the effects of alterations in PER3 expression on OSCC metastasis. Mechanistically, PER3 bound to HIF-1α via the Per-ARNT-Sim 1 domain and promoted its ubiquitination degradation. Hypermethylation at CpG site cg12258811 of PER3 promoter inhibited PER3 expression and prognosis of OSCC. Decitabine combined with LW6 upregulated PER3, downregulated HIF-1α, and inhibited lymph node metastasis of OSCC in nude mice. Our findings reveal the role and mechanism of HIF-1α regulation by PER3 and support the potential clinical application of targeting PER3 in treating OSCC metastasis.